2012
DOI: 10.1016/j.visres.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Contrast normalization contributes to a biologically-plausible model of receptive-field development in primary visual cortex (V1)

Abstract: Highlights► Contrast normalization can be introduced to a BCM neural network. ► The resulting network efficiently represents natural images. ► Contrast normalization prevents redundant representation of image structure. ► Neurally plausible model for neonatal development of receptive fields in V1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Physiological evidence [5,38] affirms that neuronal populations in the primary visual cortex (V1) of mammals exhibit contrast normalization. Neurons that respond strongly to simple visual stimuli, such as sinusoidal gratings, respond less well to the same stimuli when they are presented as part of a more complex stimulus which also excites other, neighbouring neurons.…”
Section: Bio-inspired Treatmentmentioning
confidence: 97%
“…Physiological evidence [5,38] affirms that neuronal populations in the primary visual cortex (V1) of mammals exhibit contrast normalization. Neurons that respond strongly to simple visual stimuli, such as sinusoidal gratings, respond less well to the same stimuli when they are presented as part of a more complex stimulus which also excites other, neighbouring neurons.…”
Section: Bio-inspired Treatmentmentioning
confidence: 97%
“…However, for complex cells, multiple linear spatial filters are 29 typically required, and the output of each filter is passed through a nonlinear function These types of model only describe the responses of neurons to visual stimuli and 42 cannot explain the biophysical mechanisms of complex cell responses. Several models 43 have also investigated different network architectures; these can be divided into three 44 categories: hierarchical, parallel, and recurrent (see [13] for a review). The notion of the 45 hierarchical model was proposed by Hubel and Wiesel [2], where a complex cell pools spatial phase preferences so that it is orientation selective but spatially phase invariant.…”
mentioning
confidence: 99%
“…Law and Cooper applied the BCM 235 plasticity rule to a network using natural images as input stimuli, and showed that this 236 learning rule can learn RFs like those of simple cells [43]. However, since the BCM 237 plasticity rule is the same for every neuron in the network, the learned features of the 238 network tend to be similar [44]. By incorporating response normalization, where the 239 response of a cell is normalized by the responses of other cells in the network [45], a 240 "soft" form of competition is introduced to the network.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The natural image model also produced a population of neurons with a bias toward cardinal orientations, resulting from the model learning from natural images, which themselves have a cardinal orientation bias (Willmore et al, 2012).…”
Section: The Horizontal Effectmentioning
confidence: 99%